Test and Analysis of Sludge Dewatering with a Vacuum Negative Pressure Load at the Bottom of Full Section. (14th October 2020) - Qi, Yongzheng; Wang, Zongzhi; Jiang, Pengming; Guan, Yunfei; Wang, Liyan; Mei, Ling; Zhou, Aizhao; Hou, Heying; Xu, Haoqing
Abstract : At present, the sludge production has increased sharply, and sludge treatment remains a serious problem. Rapid sludge dewatering is the key problem of sludge treatment, and the main approach for reducing the cost of the sludge treatment is to reduce the cost of sludge dewatering. In this paper, two groups of sludge dewatering tests were carried out using homemade instruments and equipment. One group was conducted without rice straw, and the other group was conducted with rice straw. The relevant mechanism was analyzed, and the results indicate that sludge dewatering with a vacuum negative pressure load of the full section at the bottom is better than mechanical sludge dewatering. The sludge dewatering effect with rice straw is better than that without rice straw. Additionally, the vacuum degree inside the sludge decreased sharply. The pore water pressure slowly dissipates during the early and late stages and quickly during the middle stage. Sludge pore water seepage does not obey Darcy's law, and sludge dewatering is intermittent.